Looking East and West for Pulpwood, Pulp and Paper : Great Britain as an Anomaly in Europe, 1860–1960 - Kuhlberg, Mark; Särkkä, Timo (Walter de Gruyter GmbH, 2024)
The years 1860 to 1960 witnessed the birth and rapid expansion of the modern pulp and paper industry. Its sine qua non was access to enormous volumes of conifer trees that grew in the northern hemisphere’s temperate and boreal forests. Predictably, countries in northern Europe with large swaths of these woodlands became home to substantial pulp and paper industries. This article explains why Great Britain represented Europe’s glaring exception to this rule. Unique circumstances allowed it to become Europe’s largest newsprint producer even though it suffered from a dearth of conifers. Britain’s newspaper publishers grew their circulations and created the largest newsprint market in Europe for most of the period under examination. To meet their exploding demand for paper, they gained control over their country’s newsprint industry. Like producers in other western European countries, they looked to Scandinavia to address their lack of domestic wood supplies, but they also exploited their imperial connection to access a prodigious supply of fibre and pulps in Canada and Newfoundland. Britain’s competitive advantage in this regard was political and not economic because tapping this distant source of raw materials was costly. Nevertheless, British producers were able to absorb the higher costs because their business was vertically integrated. However, British producers could not outrun their resource deficit forever. Changing global industry conditions after World War II caused them to lose their preponderant standing. peerReviewed